As relações afetivas e a esfera da intimidade em "O Cortiço", de Aluísio Azevedo - Rocha, Francisca Solange Mendes da (2009)
This study highlights the valuable contributions of the novel O Cortiço of Aluísio Azevedo for understanding the social context of Rio de Janeiro at the end of the nineteenth century. O Cortiço is a panel that comes out several representative types of the time. The book recounts the everyday, of an inn house in Botafogo. The residents of her neighbor, and a rich collection of blatant emotional realities experienced by the characters. Family relationships and their consequences guide the subject matter hereof. They are drawn to the various forms of interaction between the characters in the novel, including those involving adultery and prostitution. Through an analysis of the behavior of the characters, the research aims at the thesis of social and genetic determinism advocated by the author. Using the investigative method of interpretation, the study came from literary text to the analysis of the subject, the verbal context obtained by Aluísio Azevedo, and the advantage of the theoretical texts related to sociology and history.